Estado de coisas inconstitucional no sistema prisional piauiense : medidas adotadas e resultados obtidos pelo Estado do Piauí após decisão proferida pelo STF na ADPF nº 347/DF - Brasileiro, Leonardo (2022)
The de facto state of overcrowding of prisons, long provisional arrests, among other concrete problems, culminated in the filing of the Arguição de Descumprimento de Preceito Fundamental nº 347/DF, since the advancement of projects aimed at incarcerated people has a political cost that makes it uninteresting for powers subjected to popular scrutiny. In the context of the aforementioned constitutional action, the existence of an Unconstitutional State of Things in the Brazilian prison system was recognized, and in order to remedy this factual situation, in addition to the declaration, the Supreme Court determined the mandatory release of the National Penitentiary Fund so that the states could invest in their prison systems, seeking the minimum conditions of dignity and resocialization for incarcerated. It was also determined the holding of custody hearings that were already provided for in international treaties that Brazil incorporated in 1992. The context of generalized unconstitutionality has national repercussions, however the effective execution of the measures granted in precautionary measure depends on an isonomic application that considers the peculiarities regional. In this sense, the State of Piauí, especially the Piauí Judiciary, adopted measures to reverse this serious violation of fundamental rights in its prison system, especially overcrowding, such as holding custody hearings, which allows custody hearings within a maximum period of twenty-four hours after the arrest, thus preventing unnecessary precautionary arrests from protracting indefinitely; the creation of the Teresina Inquiry Center, with authority to hold custody hearings and competence to control the legality of the criminal investigation; creation of the computerized system SAAB, which prevents the defendant from staying in prison beyond the period established by law; installation of the Teresina Integrated and Penal Alternatives Center, which is responsible for supervising and monitoring the fulfillment of alternative measures to the custodial sentence; implementation of the “Ressocializar para não Prender” and Restorative Justice for Liberty projects, as proposals for the resocialization of the convict; innovative judicial decisions in the criminal execution phase to face the overcrowding of prisons, as a way of guaranteeing the fundamental rights of the prisoner. Such measures, since they are of relevant importance, represent a beginning of adequacy, given that they are facing a high stage of constitutional violation, so that many measures must be orchestrated by the powers, in a coordinated way, to overcome the state of affairs. unconstitutional in the Piauí prison system.